2000
DOI: 10.1111/0026-7902.00076
|View full text |Cite
|
Sign up to set email alerts
|

A Theory‐Based Approach to the Measurement of Foreign Language Learning Ability: The Canal‐F Theory and Test

Abstract: This article presents a rationale, description, and partial construct validation of a new theory of foreign language aptitude: CANAL‐F—Cognitive Ability for Novelty in Acquisition of Language (Foreign). The theory was applied and implemented in a test of foreign language aptitude (CANAL‐FT). Three unique features differentiate the new test from many existing tests of FL aptitude. The CANAL‐FT is grounded in cognitive theory, dynamic rather than static, and simulation‐based. This article outlines the CANAL‐F th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
120
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(133 citation statements)
references
References 31 publications
10
120
1
2
Order By: Relevance
“…This has given rise to a number of different aptitude tests (e.g. MLAT (Carroll & Sapon, 1959); Pimsleur Aptitude Battery (Pimsleur, 1966); DLAB (Petersen & Al-Haik, 1976); CANAL-FT (Grigornko, Sternberg & Ehrman, 2000); LLAMA (Meara, 2005); HiLAB (Linck et al, 2013)). These tests all have slightly different emphases in what they (claim to) measure and many are not currently available to researchers (see Skehan, 2016, for a fuller discussion).…”
Section: Introductionmentioning
confidence: 99%
“…This has given rise to a number of different aptitude tests (e.g. MLAT (Carroll & Sapon, 1959); Pimsleur Aptitude Battery (Pimsleur, 1966); DLAB (Petersen & Al-Haik, 1976); CANAL-FT (Grigornko, Sternberg & Ehrman, 2000); LLAMA (Meara, 2005); HiLAB (Linck et al, 2013)). These tests all have slightly different emphases in what they (claim to) measure and many are not currently available to researchers (see Skehan, 2016, for a fuller discussion).…”
Section: Introductionmentioning
confidence: 99%
“…In one of our studies, we devised a test of foreign-language learning ability that dynamically measured participants' ability to learn an artificial language at the time of test. The language was quite complex and required learning of many different facets, presented both orally and visually (Grigorenko, Sternberg, & Ehrman, 2000). We found that scores on our test correlated more highly with a test of foreign-language learning ability (the Modern Language Aptitude Test-MLAT) than with a test of general ability.…”
Section: There Is More To Intelligence Than Iqmentioning
confidence: 67%
“…Existing aptitude tests (e.g. MLAT (Carroll & Sapon, 1959), DLAB (Petersen & Al-Haik, 1976), CANAL-S (Grigorenko, Sternberg, & Ehrman, 2000) are general purpose instruments. They are proposed as usable for the learning of any language --in passing it should be noted that these tests, in base form, generally assume L1 English learners, but translations of some of these tests are available.…”
Section: Measuring Working Memory and The Importance Of Specific Lanmentioning
confidence: 99%